2010
DOI: 10.1097/eja.0b013e3283398ef9
|View full text |Cite
|
Sign up to set email alerts
|

Flumazenil expedites recovery from sevoflurane/remifentanil anaesthesia when administered to healthy unpremedicated patients

Abstract: Administration of a single dose of 0.3 mg flumazenil to healthy unpremedicated patients at the end of sevoflurane/remifentanil anaesthesia results in earlier emergence from anaesthesia and significantly expedites recovery. This could redefine the role of flumazenil in general anaesthesia, implicating endozepine-dependent mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 29 publications
1
24
0
3
Order By: Relevance
“…Our results are consistent with clinical studies that suggest flumazenil can reverse anesthesia even in the absence of benzodiazepines 35 . However, Schwieger and Szlam found that flumazenil had no effect on the anesthetic requirements of dogs undergoing inhaled anesthesia 51 and other studies show that flumazenil can potentiate the sedative qualities of propofol in patients undergoing minor surgery 9 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with clinical studies that suggest flumazenil can reverse anesthesia even in the absence of benzodiazepines 35 . However, Schwieger and Szlam found that flumazenil had no effect on the anesthetic requirements of dogs undergoing inhaled anesthesia 51 and other studies show that flumazenil can potentiate the sedative qualities of propofol in patients undergoing minor surgery 9 .…”
Section: Discussionsupporting
confidence: 91%
“…The results from pharmacologic experiments of flumazenil on the GABA A receptor suggest that although antagonism of the GABA A receptor is possible with flumazenil, partial agonism can also be exhibited, consistent with the pharmacological profile of a competitive antagonist with weak intrinsic agonist activity. These in vitro findings might help explain some of the variability in emergence characteristics previously shown with flumazenil administration in humans 8,34,35 .…”
Section: Discussionmentioning
confidence: 53%
“…Flumazenil, a benzodiazepine receptor antagonist, effectively reverses benzodiazepine-induced CNS depression via competitive inhibition at the GABA-A receptor-binding site [2][3][4][5][6][7][8]. Flumazenil has been beneficial for expediting patient recovery from anesthesia [9][10][11] and was previously studied in 519 patients at our center; of which, 15 were diagnosed with alcohol withdrawal [12].…”
Section: Introductionmentioning
confidence: 99%
“…Different from the study where the injection was performed 30 minutes before the end of the anesthesia, there was a study in which flumazenil was injected just before the end of the operation to investigate the effect on recovery, but only the time taken to the appearance of the recovery parameters was measured, without measuring the BIS value [6]. Since BIS decreases in a dose-dependent manner with respect to various anesthetics such as propofol, sevoflurane, and midazolam among others, it allows for measurement of the depth of anesthesia with these anesthetics [24], and is useful for measuring the degree of awareness after general anesthesia [25].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, flumazenil is used for the purpose of antagonism in general anesthesia when a benzodiazepine is used [4], but recently, a few studies have been performed testing the effect of flumazenil on recovery from general anesthesia in which no benzodiazepines were used. For example, there have been reports demonstrating a positive effect of flumazenil injection on recovery from general anesthesia that did not include benzodiazepine medication [5,6]. Additionally, a few studies have reported on the effect of inhalation anesthetics, including sevoflurane, on the GABA-A receptor [7-9].…”
Section: Introductionmentioning
confidence: 99%